An Evaporation Model for High Latitude Upland Lichen Surfaces - Stewart, Robert Bruce (My University, 1972)
Energy-budget calculations and equilibrium model estimates of evaporation from a lichen-dominated upland site in the Hudson Bay low-lands are presented. The energy budget calculations reveal that the lichen surface is relatively resistant to evaporation with an average of only 54 percent of the daily net radiation being utilized in the evaporative process. Equilibrium estimates of evaporation consistently overestimate actual evaporation by 5 and 8 percent for hourly values and daily totals respectively. A simple model, a function of the equilibrium model, is derived from a comparison of actual and equilibrium evaporation. The only inputs required for the model are net radiation, soil heat flow and screen temperatures. Tests of the model indicate that it will predict actual evaporation within 5 percent and that it can probably be applied to any high latitude surface which exhibits a relatively large resistance to evaporation.
Keywords: evaporation, high latitude, upland, lichen, surfaces, energy-budget, equilibrium